استيعاب الطلبة الناطقين بغير اللغة العربية لقواعد اللغة العربية في ضوء نظريات تعلُّم اللغات Non-native Arabic speaking students’ assimilation of Arabic linguistic rules in the light of language learning theories - Zakaria, Abd Wahab; al-farsi, hussein (IIUM Press, 2015)
مستخلص البحث